2019
DOI: 10.3390/atmos10090547
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Wind Field Retrieval Based on UHF Wind Profiler Radars and S-Band Radars Network

Abstract: The three-dimensional wind field (WPR3D) and the multiple WPR3D (M-WPR3D) associated with the passage of a stationary front was derived from observations made by a network of eight wind profiler radars (WPR) being operated by the Korea Meteorological Administration during the summer “Jangma” season. The effectiveness of the WPR3D was determined through numerical model analysis and wind profilers at three sites, and the accuracy of the M-WPR3D was validated by comparing the trajectory of the radiosonde. The dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Kottayil et al [21] validated wind measurements made with a 205 MHz radar located in Cochin, India, using a nearly co-located radiosonde with a separation of 1 km between them, and the results indicated that the standard deviations of the overall wind differences for zonal and meridional components were, respectively, 1.95 and 1.56 ms −1 . Kim et al [22] compared the wind fields retrieved from a UHF band wind profiler at 1290 MHz and S-band weather radars to those obtained by a numerical forecasting model as well as rawinsonde data. They showed that the root mean square errors (RMSEs) of the u and v components between model estimates and the wind profiler measurements were 3.39 ms −1 and 2.58 ms −1 , respectively, and the RMSE of their wind velocities was 3.16 ms −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Kottayil et al [21] validated wind measurements made with a 205 MHz radar located in Cochin, India, using a nearly co-located radiosonde with a separation of 1 km between them, and the results indicated that the standard deviations of the overall wind differences for zonal and meridional components were, respectively, 1.95 and 1.56 ms −1 . Kim et al [22] compared the wind fields retrieved from a UHF band wind profiler at 1290 MHz and S-band weather radars to those obtained by a numerical forecasting model as well as rawinsonde data. They showed that the root mean square errors (RMSEs) of the u and v components between model estimates and the wind profiler measurements were 3.39 ms −1 and 2.58 ms −1 , respectively, and the RMSE of their wind velocities was 3.16 ms −1 .…”
Section: Introductionmentioning
confidence: 99%